The Effect of Car Free Day (CFD) on Pollutant Emissions at Alternative Roads (Case Study: RE Martadinata Street, Bogor City) - Rachmawati Aida; Fithriya Yulisiasih Rohmawati; Ana Turyanti (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2019)
Car Free Day (CFD) is a social campaign aimed to reduce the dependence of people on vehicle uses, which occurs once per week in Bogor. The idea intends to decrease the vehicle emissions. However, CFD is often to cause a new problem like the congestions, which are found on the nearby alternative roads, as happened in RE Martadinata Street, Bogor City. This study aims to compare the emission load and the concentrations of pollutants in ambient air during CFD (06.00-09.00 am) and non-CFD days in alternative road. We measured the following pollutants: CO, HC, NOx, PM10 and SO2. This research first applied Fixed-Box Model to estimate concentration of pollutants, then we used the Finite Length Line Source (FLLS) to estimate dispersion of pollutants. The results showed that there was no substantial difference in pollutant emissions between CFD and non-CFD days. But if we separate between weekdays and weekend, our analysis revealed that emissions during the weekend are bigger than that of weekdays. This was consistent with an increase of number of vehicles during the weekends by 17.2%. Based on our analysis, motorcycle contributes to an increased of CO, HC, PM10 pollutants, whereas SO2 and NOx pollutants were generated by cars. Our findings suggest that a short time of CFD does not contribute a lot to reduce the emissions.